2014
DOI: 10.1016/j.bjid.2013.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculin skin testing in inflammatory bowel disease patients from an endemic area of Brazil

Abstract: Patients with IBD have TST results similar to the general Brazilian population. Within the IBD population, CD patients have a lower frequency of TST positivity than UC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…We found a higher positivity for CD, which may be related to the higher number of cases for this series. In addition, Cardoso et al found alterations in radiological findings and, perhaps, this may be justified by the socioeconomic difference of the population in question (29) . We focused on latent tuberculosis and its correlation in several aspects, such as disease classification, gender, age, work environment and others.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found a higher positivity for CD, which may be related to the higher number of cases for this series. In addition, Cardoso et al found alterations in radiological findings and, perhaps, this may be justified by the socioeconomic difference of the population in question (29) . We focused on latent tuberculosis and its correlation in several aspects, such as disease classification, gender, age, work environment and others.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have applied this surveillance test in Brazil to individuals who are candidates for biologic therapy (28,29) . Similar to our data, Brunelli et al used screening with TST to track patients in Brazil and prevent latent TB, showing the usefulness and applicability of this test in that population.…”
Section: Discussionmentioning
confidence: 99%
“…PCM Dermatology Online Journal || Case Report serology exams with false negative results may occur in limited lesions as well as in immunosuppressed patients [14]. Interestingly, CD could cause a decreased response and delayed hypersensitivity [15]. Additionally, AZA is a drug with side effects such as leukopenia and inhibition and apoptosis of T cells causing an anergic status [16].…”
Section: Case Discussionmentioning
confidence: 99%
“…84 85 86 Using purines alone can also increase the risk of LTBI reactivation. 87 88 The combination of purines with glucocorticoids and/or TNF-α antagonists is more likely to cause LTBI reactivation than purines monotherapy.…”
Section: Ibd and M Tuberculosis Infectionmentioning
confidence: 99%